Acquisition of deleterious mutations during potato polyploidization. Issue 1 (20th January 2019) - Lian, Qun; Tang, Die; Bai, Zhiyan; Qi, Jianjian; Lu, Fei; Huang, Sanwen; Zhang, Chunzhi
Summary: Potatoes ( Solanum tuberosum L.) represent an important tuber crop, worldwide. During its prolonged clonal propagation, numerous deleterious mutations have accumulated in the potato genome, leading to severe inbreeding depression; however, the shaping of this mutation burden during polyploidization and improvement is largely unknown. Here, we sequenced 20 diploid landraces of the Stenotomum group, eight tetraploid landraces, and 20 tetraploid modern cultivars, to analyze variations in their deleterious mutations. We show that deleterious mutations accumulated rapidly during the polyploidization of tetraploid potatoes. This study provides a foundation for future potato improvement. Abstract : Deleterious mutations affect the fitness of organisms. During the polyploidization of potato, the number of deleterious mutations was significantly increased. Despite of the high mutation burden, tetraploid potatoes still maintain good agronomic performance because most of the increased deleterious mutations are heterozygous.